2017
DOI: 10.1039/c7ta90221b
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Metal-functionalized covalent organic frameworks as precursors of supercapacitive porous N-doped graphene

Abstract: Correction for ‘Metal-functionalized covalent organic frameworks as precursors of supercapacitive porous N-doped graphene’ by Jorge Romero et al., J. Mater. Chem. A, 2017, 5, 4343–4351.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…[14,15] The a-C thin films have no long-range ordering although localized crystals or the crystal traces are sparsely scattered (Figure 3b). [14] A smooth ultrathin a-C film can be obtained through the synthesis utilizing covalent organic frameworks (COFs), [39][40][41] metal-organic frameworks (MOFs), [42,43] and surface-bound organic molecules. [44] COFs are a distinctive group of layered 2D crystalline supramolecules self-assembling by the π-π stacking.…”
Section: Synthesis and Doping Of The A-c Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15] The a-C thin films have no long-range ordering although localized crystals or the crystal traces are sparsely scattered (Figure 3b). [14] A smooth ultrathin a-C film can be obtained through the synthesis utilizing covalent organic frameworks (COFs), [39][40][41] metal-organic frameworks (MOFs), [42,43] and surface-bound organic molecules. [44] COFs are a distinctive group of layered 2D crystalline supramolecules self-assembling by the π-π stacking.…”
Section: Synthesis and Doping Of The A-c Thin Filmsmentioning
confidence: 99%
“…A smooth ultrathin a‐C film can be obtained through the synthesis utilizing covalent organic frameworks (COFs), [ 39–41 ] metal‐organic frameworks (MOFs), [ 42,43 ] and surface‐bound organic molecules. [ 44 ] COFs are a distinctive group of layered 2D crystalline supramolecules self‐assembling by the π–π stacking.…”
Section: Synthesis and Doping Of The A‐c Thin Filmsmentioning
confidence: 99%
“…[146][147][148][149][150][151] The coordination heteroatoms can be doped in situ on the carbon substrate formed by carbonization to modulate the electronic structures of MNPs or single atom sites and can also induce the metal precursors to form various functional metal compounds at high temperature, such as metal suldes, metal phosphides, metal nitrides, etc., which are very difficult to make into ultra-ne sizes by conventional methods. [152][153][154][155][156][157][158][159] Wu et al reported an organic ligand CCP method to synthesize a Co single-atom catalyst and regulated the electrocatalytic CO 2 reduction performance of the catalyst by adjusting the coordination number of a single Co site (Fig. 14a).…”
Section: Coordination-connement Pyrolysismentioning
confidence: 99%
“…4d). 42,43 On the other hand, the cycling stability of supercapacitor electrode materials is also the embodiment of their excellent performance. As shown in Fig.…”
mentioning
confidence: 99%